BLENDED LEARNING STRATEGIES IN TEACHING ENGLISH GRAMMAR TO NON-NATIVE SPEAKERS - Allayorova Zebiniso Boymuartovna; Elboyeva Shaxnoza Azim qizi; Yuldoshova Shaxlo Yaqub qizi (TADQIQOTLAR, 2025)
Abstract Blended learning combines traditional face-to-face instruction with digital resources, enhancing the learning experience for non-native English speakers. This article explores various blended learning strategies specifically designed to improve English grammar instruction. It discusses the advantages, challenges, and best practices in implementing a blended approach to teaching grammar effectively.